Copper‐Catalyzed Alkoxylation as Key Step to Convert Isatin to Oxazinoindol‐2‐one Derivatives. Issue 16 (24th April 2018) - Christodoulou, Michael S.; Giofrè, Sabrina; Broggini, Gianluigi; Dalla Via, Lisa; Mazza, Alberto; Beccalli, Egle M.
Abstract: The treatment of N ‐alkyl‐5, 7‐dibromoisatin derivatives through the copper‐catalyzed sequential processes consisting of intra/intermolecular alkoxylation/amination or double alkoxylation provided the pyrrolo[1,  2, 3‐ de ]‐1, 4‐benzoxazine derivatives. Moreover, the alkoxylation/arylation process proceeded in a one‐pot fashion under tandem copper‐palladium catalysis affording 5‐(hetero)aryl substituted hetero‐tricyclic systems. Biological evaluation of the synthesized compounds showed antiproliferative activity on the low micromolar range. Abstract : Starting from 5, 7‐dibromoisatin we developed a copper‐catalyzed sequential processes for the synthesis of oxazinoindole‐2‐one derivatives. The new pathway consisted of a intra/intermolecular alkoxylation/amination or double alkoxylation providing the pyrrolo[1,  2, 3‐ de ]‐1, 4‐benzoxazine derivatives. Moreover, the alkoxylation/arylation process was developed as a one‐pot procedure using the tandem copper‐palladium catalysis, providing 5‐(hetero)aryl substituted oxazinoindole‐2‐ones. Due to the interest of the scaffold, a preliminary biological evaluation for some of the compounds showed antiproliferative activity on the low micromolar range.